Incomplete penetrance of MITF gene c.943C>T mutation in an extended family with Waardenburg syndrome type II. (August 2020) - Alehabib, Elham; Alinaghi, Somayeh; Pourfatemi, Fatemeh; Darvish, Hossein
Abstract: Waardenburg syndrome (WS) is a group of genetic disorders that often determined by abnormal pigmentation and hearing impairment. Four subgroups of disease are recognized according to physical characteristics and involved genes. Mutation in the genes, MITF, SOX10, SNAI2, PAX3, KIT and KITLG are related to Waardenburg syndrome type II. In this study, we performed exome sequencing in a WS2 proband and detected a heterozygous non-sense variation in MITF. Clinical features, pedigrees investigations and molecular segregation revealed autosomal dominant inheritance with incomplete penetrance. To our knowledge it's the first evidence about incomplete penetrance of WS2 related to MITF gene.